Factors Associated with Underweight in Children Aged 6-59 Months in the Kibuye Health District, Gitega Health Province, Burundi - Aloys, Nzigamasabo; Jeanette, Ndayishimiye; Bonaventure, Niyoyankana; Paterne, Nahimana (International Journal of Child Health and Nutrition, 2025)
The study, conducted in the Kibuye health district in Burundi, aimed to investigate the factors associated with underweight children aged 6-59 months. An analytical cross-sectional study was conducted on a sample of 273 households with at least one randomly selected child aged 6-59 months in the Kibuye, Burundi health district. Socio-demographic, socio-economic, child morbidity, behavioral, and environmental data were collected using a structured questionnaire. Children’s weight was measured using a standard procedure (seca scale), height was measured using a UNICEF standard height board, and age was obtained from the birth certificate. Anthropometric data were analyzed using Emergency Nutrition Assessment (ENA for Smart) software. Modeling was performed using logistic regression to eliminate confounding factors, and all independent variables whose significance level was less than or equal to 20% in the bivariate analysis were included to explore factors associated with underweight children aged 6-59 months. In this study, the prevalence of underweight was 32.9%. After multivariate analysis, child age (OR=7.82, 95% CI = [2.21-27.6]), child gender (OR=2.61, 95% CI = [1.31-5.23]), maternal education level (OR=0, 32, 95% CI = [0.15-0.65]), exclusive breastfeeding (OR=0.28, 95% CI = [0.13-0.60]), latrine type (OR=8.08, 95% CI = [1.06-61.38]), water source (OR=2.76, 95% CI = [1.33-5.74]), mothers’ knowledge of a balanced diet (OR=0.23, 95% CI = [0.08-0.64]) and knowledge of the consequences of malnutrition (OR= 0.21, 95% CI = [0.07-0.61]) were identified as factors significantly associated with underweight children aged 6-59 months in the Kibuye health district.